생산자조직 경제사업 활성화 지원방안에 관한 연구 - 황의식 (한국농촌경제연구원, 2006)
The purpose of the study is to establish the business innovation strategies of the National Agricultural Cooperative Federation(NACF). It is top priority to revitalize marketing First, analyzed the business structure of the NACF, then summarized the current condition and problems. Second, evaluated the adequacy of the plan to revitalize marketing & sales business, which was prepared by the NACF and submitted to the Presidential Commission for the NACF Reform. Third, analyzed why the NACF has been lost money at marketing & supply operation then derived business innovation strategies to build a self-reliance foundation. Fourth and last, came up with basic principle, system, and rule modifying scheme for plan to revitalize marketing & sales business and proposed our own plan coping with market opening of agricultural products, and the change in marketing environment. Researchers: Eui-Sik Hwang, Sung-Jae Park, Hogun Chong, Yongwon Cho Research Period: 2006.6 ~ 2006.12 E-mail address: eshwang@krei.re.kr